Metode Pembelajaran Klinik pada Praktik Profesi Mahasiswa Keperawatan - Etlidawati Etlidawati; Diyah Yulistika (Universitas Faletehan, 2022)
Clinical learning is a very important activity at the stage of professional nurse program. In this activity, the students implement theories obtained during college. The learning process requires a good method in order to achieve learning objectives. Furthermore, clinical supervisors must identify the existed obstacles so that they can determine the clinical learning method to be used. The purpose of the study was to describe some clinical learning methods in the practice of professional nurse program and the obstacles in the clinical learning. It was a descriptive analytical study with cross-sectional approach. The samples were 88 students of professional nurse program, selected by using the accidental sampling technique. The bivariate analysis used chi square statistical test. The test results showed that experiential learning method and preceptorship method was highly implemented (respectively 22.7%), observation learning method was frequently implemented (34%), the conference method was rarely used (34.0%), and the nursing clinic method was extremely sparse (64.7%). The most frequent obstacle in clinical learning came from clinical supervisors (65.9%). The statistical results obtained p value 0.001 < 0.05, which can be concluded that there was a relationship between methods and obstacles of clinical learning.